The Influence of Asset Structure, Firm Size, Profitability and Business Risk on Capital Structure in Companies Listed on the IDX - Kartika; Fatimah; Ladewi, Yuhanis (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
This study aims to determine the effect of asset structure, firm size, profitability and business risk on capital structure in companies listed on the Indonesian Stock Exchange (IDX). The object of research is property, real estate and building construction employee. The type of research used is asosiatif research with secondary data. The population was 91 companies; the research sample used purposive sampling method that collected 20 samples of the companies with 2016-2020 of the study period. The technical analyses used were multiple linear regression analysis. The result showed that the variables of asset structure did not have a significant influence on capital structure, while the firm size, profitability and businesse risk variable gave a significant influence on capital structure.